2019
DOI: 10.1007/s00227-019-3563-8
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the effects of size, habitat and invertebrate biodiversity on parasite prevalence in the Caribbean spiny lobster

Abstract: The spiny lobster Panulirus argus is an important benthic mesopredator and a major fishing resource across the Wider Caribbean region. This species is host to the pathogenic virus PaV1 and metacercariae of Cymatocarpus solearis, a digenean trematode whose first intermediate host remains unknown. Previous studies found that the probability of infection with PaV1 was higher in juvenile lobsters and in densely vegetated habitats (suggesting that marine vegetation can be an environmental reservoir for PaV1), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…As previously noted, some studies have reported a higher PaV1 prevalence in densely-vegetated areas compared to poorly-vegetated areas even after accounting for the significant effect of lobster size, suggesting that vegetation may be acting as an environmental reservoir for the disease [14,15]. This notion has been supported by a recent study [16] in which the probability of infection with PaV1 was found to be higher in lobsters inhabiting more vegetated habitats, but further proposing that either marine vegetation or fauna that live associated with vegetated habitats, or both, may be reservoirs of PaV1.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…As previously noted, some studies have reported a higher PaV1 prevalence in densely-vegetated areas compared to poorly-vegetated areas even after accounting for the significant effect of lobster size, suggesting that vegetation may be acting as an environmental reservoir for the disease [14,15]. This notion has been supported by a recent study [16] in which the probability of infection with PaV1 was found to be higher in lobsters inhabiting more vegetated habitats, but further proposing that either marine vegetation or fauna that live associated with vegetated habitats, or both, may be reservoirs of PaV1.…”
Section: Introductionsupporting
confidence: 67%
“…To examine potential ecological differences among sampling zones and over time, percent cover of different types of substrate, habitat complexity, and invertebrate diversity were estimated in each zone [16] for two contrasting seasons (June and November) over two years (2016 and 2017), yielding four sampling periods. In each period, six transects, each 25 m in length, were laid parallel to the reef and the coast in each zone.…”
Section: Habitat Characterizationmentioning
confidence: 99%
See 3 more Smart Citations